Función social de la escritura - Riesco Terrero, Ángel (Revista General de Información y Documentación, 2002)
The present work is an attempt at a critical analysis and global assessment of a whole group of aspects both of a graphical-structural and interpretive type and those of a cultural, social, pedagogical, anthropological, interrelational, cognoscitive and functional nature and materialized in language: in the language of thinking, speaking and writing, in other words in the written form and in written documents. At the same time it is a proposal for objective criteria for determining —within a scale of values— what priority and level should be given, in study and teaching, to each of them, in the first place for themselves and, in the second place from the point of view of their meaning and function.
Keywords: Language; Writing; Paleography; Written documentation